2020
DOI: 10.1038/s41598-020-64770-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of Stereotactic Body Radiation Therapy (SBRT) for adrenal gland metastases: A multi-center retrospective study from China

Abstract: To evaluate the efficacy and safety of CyberKnife Stereotactic Body Radiation Therapy (SBRT) in the treatment of adrenal gland metastases (AGM), we designed a large-scale multicenter retrospective study to report the safety and efficacy of SBRT for inoperable AGM. In this study, 75 (61 males, 14 females) patients with 84 AGM and Karnofsky performance score ≥70 were treated by SBRT from October 2006 to January 2017. Of these, the purpose of treatment were controlling all known metastatic sites for 21 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 34 publications
6
26
1
Order By: Relevance
“…This was done to facilitate comparability with other studies which mostly used unadjusted values. 30,34,42 The unadjusted LC differed between the arms and was in line with the two other larger datasets: after prescribed doses of 100, 80 and 60 Gy (BED10), Chen et al 32 found in their meta-analysis 3DCRT/IMRT were limited and statistical differences in FFLP might have been obscured by differences in histology, lesion size and systemic treatments. Furthermore, the minimum BED10 in the SBRT group was 50 Gy, a dose which is well below the BED10 of 100 Gy which is typically considered ablative, for example, in lung cancer which was the largest subgroup.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This was done to facilitate comparability with other studies which mostly used unadjusted values. 30,34,42 The unadjusted LC differed between the arms and was in line with the two other larger datasets: after prescribed doses of 100, 80 and 60 Gy (BED10), Chen et al 32 found in their meta-analysis 3DCRT/IMRT were limited and statistical differences in FFLP might have been obscured by differences in histology, lesion size and systemic treatments. Furthermore, the minimum BED10 in the SBRT group was 50 Gy, a dose which is well below the BED10 of 100 Gy which is typically considered ablative, for example, in lung cancer which was the largest subgroup.…”
Section: Discussionsupporting
confidence: 77%
“…16,[22][23][24][25][26][27][28][29][30][31][32][33] Larger analyses include a retrospective database analysis conducted in Asian patients (n = 75) reporting 1-year LC rate of 83%. 34 Furthermore, multiple prospective and retrospective monocentric studies were included in a recent meta-analysis conducted by Chen et al, which reported a pooled 1-year LC rate of 82% with a strong association of prescribed doses and LC rates. 32 We conducted this multicenter database analysis of patients with adrenal metastases treated with SBRT or fractionated highly conformal RT (3DCRT/IMRT) within the framework of the SBRT database initiative of the Working Group Radiosurgery and Stereotactic Radiotherapy of the German Society for Radiation Oncology (DEGRO).…”
Section: What's New?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the doses of radiation used in these trials (with the exception of the patients in the MDACC trial randomized to combinedmodality therapy in whom 50 Gy in 4 fractions was deemed feasible) resulted in BEDs that are well below that of ablative approaches in which BEDs of 100 Gy and greater are delivered. Given that ablative BEDs have been demonstrated to be imperative for optimal local control of irradiated metastases (126)(127)(128)(129) and that degree of local response to SBRT is an important predictor of survival (112) future randomized studies investigating the role of SBRT in combination with ICB should utilize ablative doses of radiation therapy in an attempt to maximize the potential for therapeutic response with this liaison. Although the currently reported randomized studies do support the safety of SBRT in combination with ICB, it is important that future studies utilizing higher doses of SBRT evaluate this further as these, along with ongoing phase III studies investigating the combination of ablative doses of radiation with ICB in the definitive setting, will help to determine the safety of this approach.…”
Section: Comparative Studies Evaluating the Addition Of Sbrt To Icbmentioning
confidence: 99%
“…In addition to attempts to increase the therapeutic ratio of SBRT and ICB, by altering the tumor microenvironment, improvements in metastasis-directed SBRT have the potential to significantly improve the efficacy of this treatment approach. As previously discussed, given that ablative BEDs are crucial for optimizing the local control of irradiated metastases (126)(127)(128)(129) and that local response to SBRT has been correlated with survival (112), randomized studies investigating the role of ablative doses of SBRT in combination with ICB are needed. Historically, technical and practical considerations have largely limited the feasibility of multi-site SBRT using ablative doses for patients with metastatic disease, though several recent innovations have significantly decreased these limitations.…”
Section: Innovations In Metastasis-directed Sbrtmentioning
confidence: 99%